2016
DOI: 10.14218/jcth.2016.00009
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 as a Genetic Determinant of Risk for and Severity of Non-alcoholic Fatty Liver Disease Spectrum

Abstract: Background and Aims: Patatin-like phospholipase domain protein 3 (PNPLA3) polymorphisms (rs738409 C>G) are associated with non-alcoholic fatty liver disease (NAFLD). We performed a systematic review and meta-analysis to examine the association of PNPLA3 polymorphisms with the spectrum and severity of this disease. Methods: Studies evaluating the association between the PNPLA3 polymorphism spectrum (fatty liver, steatohepatitis, cirrhosis, and hepatocellular carcinoma) and NAFLD were included. Pooled data are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…In fact, our data support that more aggressive disease with higher fibrosis scores was associated with rs738409 variation–subjects with higher activity scores (A > 2) were 17 times more likely to be GG homozygous than to be homozygous for the C allele; and subjects with liver fibrosis were 7.4-fold more likely to be GG homozygous than to be CC. Lack of significant association between histological steatosis grade and rs738409 genotype was observed in at least two other case-control studies[ 46 , 47 ]; and an association between PNPLA3 and inflammation activity and fibrosis in NAFLD has also been found in other studies[ 21 , 23 , 25 ]. Our study, however, was limited by the fact that only 44% of the patients underwent liver biopsy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In fact, our data support that more aggressive disease with higher fibrosis scores was associated with rs738409 variation–subjects with higher activity scores (A > 2) were 17 times more likely to be GG homozygous than to be homozygous for the C allele; and subjects with liver fibrosis were 7.4-fold more likely to be GG homozygous than to be CC. Lack of significant association between histological steatosis grade and rs738409 genotype was observed in at least two other case-control studies[ 46 , 47 ]; and an association between PNPLA3 and inflammation activity and fibrosis in NAFLD has also been found in other studies[ 21 , 23 , 25 ]. Our study, however, was limited by the fact that only 44% of the patients underwent liver biopsy.…”
Section: Discussionmentioning
confidence: 83%
“…The first GWA study in NAFLD identified a single highly significant association between increased hepatic TG content and the PNPLA3 [ 17 ]. Subsequent studies demonstrated that this variant was also associated with the progression of NAFLD in different ethnic populations around the world[ 21 , 25 , 26 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This effect seems to be more pronounced in normal-weight subjects than in overweight subjects [ 54 , 55 ]. The PNPLA3 variant allele rs738409 C>G has been associated with the risk and severity of NAFLD (inflammation, and progression to fibrosis) and even with HCC development [ 56 ]. PNPLA3 is a strong modifier of the natural history of NAFLD and can be considered as a potential target for therapy.…”
Section: Pathophysiological and Molecular Mechanisms Of Non-alcohomentioning
confidence: 99%
“…Patatin-like phospholipase domain-containing protein 3 ( PNPLA3 ) genetic variant is the strongest genetic risk factor for the development of NASH ( 17 ). Indeed, studies have shown that individuals carrying the PNPLA3 (rs738409) variant have about a threefold increased likelihood of having NASH ( 18 20 ). Moreover, single-nucleotide polymorphisms (SNPs) in the transmembrane 6 superfamily member 2 ( TM6SF2 rs58542926), membrane-bound O-acyltransferase domain containing 7 ( MBOAT7 rs641738), and 17-beta-hydroxysteroid dehydrogenase 13 ( HSD17B13 rs72613567) genetic variants are also associated with greater susceptibility to NASH ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%